(untitled) (Contemporary Mathematics, 2024)
In this paper, we determine a single server retrial queuing system with finite capacity, F-policy, balking, reneging and server maintenance. The arriving customer when notices the server becomes free, then they get service immediately. In case server becomes busy, the customers are move to either orbit or may balk the system. In the orbit, after some random time the customer repeats their attempts for service. The customers are waiting in the orbit for longer time become impatient and leaves the orbit without getting service. Once the number of customers in the orbit reaches its full capacity then the arrival of customer is not allowed to enter into the orbit. The new customer is allowed into the orbit when the F-policy level is reached. If no more customer in the orbit, server will move to the vacation. By using recursive technique, the steady state distributions are obtained and we have developed various performance measures.